2022
DOI: 10.1107/s2056989022007113
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and Hirshfeld surface analysis of a new polymorph of (E)-2-(4-bromophenyl)-1-[2,2-dibromo-1-(3-nitrophenyl)ethenyl]diazene

Abstract: A new polymorph of the title compound, C14H8Br3N3O2, (form-2) was obtained in the same manner as the previously reported form-1 [Akkurt et al. (2022). Acta Cryst. E78, 732–736]. The structure of the new polymorph is stabilized by a C—H...O hydrogen bond that links molecules into chains. These chains are linked by face-to-face π–π stacking interactions, resulting in a layered structure. Short inter-molecular Br...O contacts and van der Waals interactions between the layers aid in the cohesion of the crystal pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A search of the Cambridge Structural Database [27] for similar structures with the (E)-1-(2,2-dibromo)-2-(4-bromophenyl)diazene unit showed that the eleven closest are those of CSD refcodes TAZDIL (I) [28], HEHKEO (II) [29], ECUDAL (III) [30], PAXDOL (IV) [31], GUPHIL (V) [1, HONBUK (VI) [13], HONBOE (VII) [13], HODQAV (VIII) [20], XIZREG (IX) [14], LEQXOX (X) [19] and LEQXIR (XI) [19].…”
Section: Table 2 Experimental Detailsmentioning
confidence: 99%
“…A search of the Cambridge Structural Database [27] for similar structures with the (E)-1-(2,2-dibromo)-2-(4-bromophenyl)diazene unit showed that the eleven closest are those of CSD refcodes TAZDIL (I) [28], HEHKEO (II) [29], ECUDAL (III) [30], PAXDOL (IV) [31], GUPHIL (V) [1, HONBUK (VI) [13], HONBOE (VII) [13], HODQAV (VIII) [20], XIZREG (IX) [14], LEQXOX (X) [19] and LEQXIR (XI) [19].…”
Section: Table 2 Experimental Detailsmentioning
confidence: 99%